التضمين التربوي لمعاني لفظ "القلب" في القرآن الكريم - Dedih Wahyudin; Nisa Fitri Ilmiawati (Jurnal Pendidikan Islam, 2013)
Based on the contradiction among educational experts in interpreting the word al-qalb on the Holy Quran . Most interpret the "mind" and others interpreted with “heart” as there is no common word. On that basis, this study aimed to dissect the meaning of al-qalb on the Holy Qur'an with semantic approach . The method used in this study is a content analysis. The method is appropriate for the aspect of sentence context surrounding the word al-qalb in a variety of verses and letters . From the results of the study concluded that the word al-qalb on the Holy Qur'an contains three meanings: 1) the place of faith and emosion ; 2 ) mind, and 3 ) the spirit or lives . Thus, the contradiction among educational experts can actually be met within the context of the sentence in the Holy Qur'an. This also has implications for understanding the cognitive aspects of education, especially coaching (sense) and spiritual aspects (faith) .